Construction and efficacy of recombinant Newcastle disease virus co-expressing VP2 and VP3 proteins of very virulent infectious bursal disease virus - Tongfei Liu; Lin Lin; Yun Pan; Xiaoling Lin; Ming Liang; Guanming Shao; Keyu Feng; Yaxin Liu; Xinheng Zhang; Qingmei Xie (Poultry Science)
Infectious bursal disease (IBD), triggered by the infectious bursal disease virus (IBDV), poses a substantial risk to the poultry industry due to its immunosuppressive nature and the emergence of highly virulent strains. Traditional vaccination strategies have limitations, prompting the need for novel approaches. This study aimed to develop a recombinant Newcastle disease virus (NDV) vector vaccine co-expressing IBDV VP2 and VP3 proteins to enhance immunogenicity and protective efficacy against IBDV. The recombinant Newcastle disease virus (rNDV) expressing both VP2 and VP3 (rNDV-VP2-VP3) was generated and compared to rNDV expressing VP2 alone (rNDV-VP2). The genetic stability and growth pattern of rNDV were evaluated and its immunogenicity was assessed in specific pathogen free (SPF) chickens. rNDV-VP2-VP3 vaccines induced higher levels of neutralising antibodies, no damage to immune organs, and significantly lower viral loads in the bursa of the falciparum. rNDV-VP2 group showed partial protection, while the placebo group exhibited severe lesions and higher mortality, suggesting that the vaccine was effective in preventing IBDV-induced damage. These findings suggest that co-expression of VP2 and VP3 in NDV vectors is a viable strategy for the development of an effective IBDV vaccine, providing a safe and effective method for controlling IBD in poultry.